2022
DOI: 10.22146/mot.72210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Flavonoid, Total Phenolic, and Antioxidant Activity of Etlingera elatior (Jack) R.M.Sm Flower, Fruit, and Leaf

Abstract: Etlingera elatior (E. elatior) plant has long been used as a kitchen spice and daily food. E. elatior has potential as an antioxidant because it contains polyphenol and flavonoid compounds widely found in the leaves, fruit, and flowers. This study measures the total flavonoid content, total phenol content, and antioxidant activity using the ABTS method. Total phenol content was determined by the Follin-Ciocalteu method and total flavonoid content was determined by the Aluminium Chloride method. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Phytochemical analysis by Juwitaningsih et al (2016) revealed the content of two pyrones compounds with antibacterial activities from the fruit extract of A. malaccensis, a giant Zingiberaceae herb bearing massive fruits found in this study. The fruit of E. elatior or torch ginger, which is very well known for its unique aromatic flower commonly used as cooking ingredients, was reported as having the highest flavonoid and phenolic content compared to flowers and leaves, and thus having beneficial antioxidant properties (Safrina et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical analysis by Juwitaningsih et al (2016) revealed the content of two pyrones compounds with antibacterial activities from the fruit extract of A. malaccensis, a giant Zingiberaceae herb bearing massive fruits found in this study. The fruit of E. elatior or torch ginger, which is very well known for its unique aromatic flower commonly used as cooking ingredients, was reported as having the highest flavonoid and phenolic content compared to flowers and leaves, and thus having beneficial antioxidant properties (Safrina et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Kadar fenolik dan flavonoid tertinggi ditemukan pada ekstrak daun. Bagian tanaman kecombrang yang dilaporkan memiliki aktivitas antimikroba adalah batang, daun, bunga, dan buah (Adini et al, 2023;Dasi & Leliqia, 2022;Farida & Maruzy, 2016;Resna et al, 2021;Rokhyani, 2015;Safrina et al, 2022;Saudah, Ernilasari, et al, 2021;Saudah, Zumaidar, Darusman, Fitmawati, Roslim, & Juliantari, 2022;Susana et al, 2018;Syarif et al, 2015). Khasiat kecombrang secara tradisional dikembangkan sebagai penambah rasa dan pengawet untuk alami untuk makanan.…”
Section: Pendahuluanunclassified